Cross-sectional study of the frequency of helminths and protozoa in buffaloes in the state of Rio de Janeiro, Brazil - Da Silva, Jenevaldo Barbosa [UNESP]; Do Nascimento Corrêa, Fabíola; De Meireles, Gisele Santos; Flausino, Walter; Da Fonseca, Adivaldo Henrique (My University, 2014)
Buffaloes and cattle are affected by a large number of helminth and protozoan common to these hosts. Although studies related to prevalence, symptoms and intensity of helminth and protozoan infections of the gastrointestinal tract of cattle are vast, the same is not true for buffaloes, particularly in Latin America. Thus, through a cross-sectional study aimed to determine the prevalence of gastrointestinal parasites in buffaloes in the state of Rio de Janeiro, Brazil. The study included six mesoregions the state of Rio de Janeiro. The average data of faecal egg counts were compared using Kruskal-willis and the percentages of infective larvae form submitted to chi-square (X2), both at 5% probability. Haemonchus spp., Trichostrongylus spp., Cooperia spp., Oesophagostomum spp., Bunostomum spp., Trichuris spp., Strongyloides papilosus, Toxocara vitulorum, Moniezia expansa and coccidia Eimeria spp. were observed by counting the eggs and oocysts in the feces. Although there have been anemic animals, mean corpuscular volume, hematocrit, total plasma protein and fibrinogen levels remained within the normal range. We observed an inverse correlation between counting helminth eggs in feces and hematocrit (r = -0 75.2, P <0.05). Although the six mesoregions the state of Rio de Janeiro have different climatic conditions, it was observed that, regardless of the region, the animals showed parasitized by nematodes, cestodes and protozoa.
Estudo transversal da frequência de helmintos e protozoários em búfalos no estado do Rio de Janeiro, Brasil
Keywords: Buffaloes; Cestodes; Nematodes; Protozoa